2023
DOI: 10.4149/neo_2022_221007n992
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and therapy of chemotherapy-induced peripheral neuropathy: a review of recent findings

Abstract: Chemotherapy-induced peripheral neuropathy is one of the most frequent dose-limiting side effects, observed in patients receiving antineoplastic agents, persisting for up to two years after completing treatment, greatly affecting both the course of chemotherapy and patients' quality of life. Approximately 20 to 85% of patients treated with neurotoxic chemotherapy will develop peripheral neuropathy and there is considerable variability in its severity among patients. The main symptoms are numbness, paresthesia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…Peripheral neuropathy (PN) is associated with several diseases including diabetes, infections, autoimmunity, malignancy, and several metabolic diseases [ 2 ]. The most common causes of PN are diabetes and treatment with chemotherapy [ 3 ] with prevalence exceeding 50% in people with diabetes [ 4 ] and approximately 20 to 85% in patients treated with chemotherapy [ 5 ]. The exact mechanisms and pathogenesis of diabetic peripheral neuropathy (DPN) and chemotherapy-induced peripheral neuropathy (CIPN) remain unclear, although it has been suggested that both share mitochondrial dysfunction as a common pathogenic mechanism [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral neuropathy (PN) is associated with several diseases including diabetes, infections, autoimmunity, malignancy, and several metabolic diseases [ 2 ]. The most common causes of PN are diabetes and treatment with chemotherapy [ 3 ] with prevalence exceeding 50% in people with diabetes [ 4 ] and approximately 20 to 85% in patients treated with chemotherapy [ 5 ]. The exact mechanisms and pathogenesis of diabetic peripheral neuropathy (DPN) and chemotherapy-induced peripheral neuropathy (CIPN) remain unclear, although it has been suggested that both share mitochondrial dysfunction as a common pathogenic mechanism [ 6 ].…”
Section: Introductionmentioning
confidence: 99%